Fostering Environmental Awareness and Responsibility in Young Students Through A Zero Waste Lifestyle - Amin Pujiati; Sinta Saraswati; Bestari Dwi Handayani; Silvia Margaret (Universitas Negeri Semarang, 2025)
Environmental awareness, when nurtured from an early age, can develop into a positive habit that becomes embedded in one’s daily life. This community service partnership program was implemented at PAUD Mutiara Kids in Temanggung as a concrete step to build environmental awareness among young learners. Based on evaluations conducted by the community service team, 92% of the students were already able to distinguish between organic and non-organic waste. However, practical skills in waste utilization were still lacking, particularly in using recycled materials for educational purposes. In addition, environmental values had not yet been integrated into students’ daily routines. To address these issues, the “Zero-Waste Lifestyle” program was introduced as a strategic solution to empower teachers, students, and school staff. The program consisted of three key activities: (1) Introducing and promoting the “Zero-Waste Lifestyle” as a method for developing environmental literacy, (2) Facilitating collaborative workshops to create educational toys from recycled materials through the Pancasila Student Profile Strengthening Project (P5), and (3) Cultivating environmentally responsible behavior through consistent waste sorting habits. The program led to positive behavioral changes in students, particularly in waste management, and helped foster an environmental awareness aligned with the broader goals of sustainable development.